Mean and fluctuating velocity fields of a diamond turbulent jet - 徐敏义 张健鹏 米建春 Nathan G.J. Kalt P.A.M (Chinese physics B, 2013)
The present paper reports the first investigation on a turbulent jet issuing from a diamond orifice（hereafter termed a ＂diamond jet＂） with an aspect ratio of 1.7.Velocity measurements were conducted in the transitional region,and the exit Reynolds number of the jet was 50000.For comparison,a round jet with identical normalized boundary conditions was also measured.It is shown that the diamond jet decays and spreads faster than the round jet does over the measured flow region.The axis-switching phenomenon is observed in the diamond jet.Although both jets display primary coherent structures in the near field,these structures are found to break down more rapidly in the diamond jet,due to the higher three-dimensionality of the flow.Moreover,the streamwise components of the Reynolds normal stress and all the shear stresses reach their maxima around the location of the maximal mean shear while the maxima of the lateral components of the Reynolds normal stresses occur around the centreline of the jet.